The role of self-control and conformity to adolescent aggressiveness - I Gede Widharma Saskara Putra; David Hizkia Tobing (Journal Of Social Science (JoSS), 2023)
Teenagers are always associated with social problems because of several changes in them, one of which is physical changes. When adolescents' physical and emotional changes have not reached maturity like adults, adolescents tend to have difficulties in facing these challenges, so feelings of depression will arise within adolescents. Feelings of pressure tend to lead adolescents to aggressive actions. The purpose of this study is to determine the relationship between self-control and conformity to adolescents' aggressiveness in the city of Denpasar. The subjects of this study were 104 students who attended SMA Negeri 6 Denpasar. Measuring tools used in this study are the aggressiveness scale, self-control scale and conformity scale. The analysis technique used in this study is multiple regression. The results of the multiple regression test showed a regression coefficient of 0.610, a coefficient of determination of 0.373 with a significance level of 0.000 (p <0.05), thereby proving that there is a role between self-control and conformity to adolescent aggressiveness in Denpasar City. The standardized beta coefficient value for self-control was 0.393 with a t-value of 4,656 and a significance level of 0.000 (p <0.05), so it can be said that the self-control variable plays a positive role in increasing aggressiveness. The conformity variable has a standardized beta coefficient of 0.348, with a t value of 4,122 and a significance level of 0.000 (p <0.05), so it can be said that conformity plays a positive role in increasing aggressiveness.